PENGELOLAAN KEWIRAUSAHAAN DAN MANAJEMEN KEUANGAN BAGI WIRAUSAHA PEMULA DI KECAMATAN GUNUNG PUTRI BOGOR - Abdurrohman Abdurrohman; Anis Fuad Salam (LPPM Universitas Bina Bangsa, 2023)
The purpose of implementing this service is to provide motivation and enthusiasm for MSME actors to do entrepreneurship, increase the creativity and innovation of MSME actors, and provide knowledge about the importance of recording financial transactions through simple bookkeeping. This activity was carried out in order to help solve problems for novice entrepreneurs in managing their business. The form of this service activity is training (workshop) related to entrepreneurship and financial management issues which was attended by 30 activity participants. In the implementation of the training materials, practice was inserted on how to become a successful entrepreneur and the practice of keeping financial reports. Furthermore, to further solidify the material, the final session was opened for questions and answers and discussion. The suggestion from this activity is that there is a need for further assistance in the field and control over the implementation of entrepreneurial management activities